2018
DOI: 10.15244/pjoes/75963
|View full text |Cite
|
Sign up to set email alerts
|

Parent Flood Frequency Distribution of Turkish Rivers

Abstract: Determining the probability distribution (PD) of such random events as floods by estimating their behavior has always been a significant problem. Identifying the appropriate PD of floods is probably the most important step in flood frequency analysis. Accordingly, many studies all over the world have investigated how to determine an appropriate PD of floods [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The selection of techniques for assessing flood frequency in specific conditions depends on severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Prior work demonstrated that selecting one distribution that provides the best fit to annual maxima is difficult over a large hydrologically heterogeneous region due to the high sample variance of the L-moments (Asikoglu, 2018;Salinas et al, 2014a). To reduce the noise and guide model selection, we compute a weighted moving average (WMA) of neighboring L-skew and their corresponding L-kurtosis proportional to record length.…”
Section: Distributionmentioning
confidence: 99%
“…Prior work demonstrated that selecting one distribution that provides the best fit to annual maxima is difficult over a large hydrologically heterogeneous region due to the high sample variance of the L-moments (Asikoglu, 2018;Salinas et al, 2014a). To reduce the noise and guide model selection, we compute a weighted moving average (WMA) of neighboring L-skew and their corresponding L-kurtosis proportional to record length.…”
Section: Distributionmentioning
confidence: 99%
“…First one refers to at-site flood frequency analysis while the second one as regional flood frequency analysis. In at-site frequency analysis, we analyze the results of each site or station individually instead of grouping the information from all sites (Zin et al, 2009;Seckin et al, 2011;Ahmad et al, 2015Ahmad et al, , 2016a; Afreen and Muhammad, 2012;Rahman et al, 2013;Asikoglu, 2018). At-site frequency analysis is not a promising technique in the presence of small data and non-availability of data at ungauged stations.…”
Section: Introductionmentioning
confidence: 99%